Learning Management Model to Promote Analytical Thinking by Applications for Youth in the Digital Era - Charoenket, Ketkaew; Patthawiwat, Kanchana; Suwanwong, Charin (Journal of Behavioral Science for Development, 2024)
The learning management model it is another form of learning. that uses the application as a tool to promote analytical thinking for youth in the digital age with a flexible and easy to access anywhere anytime, aimed at promoting analytical thinking among youths in the digital age through applications seeks to develop analytical thinking by integrating concepts from various disciplines, including constructivism theory, self-regulation, social support, and connectivism theory. This framework aims to guide learners through the following steps: 1) problem identification or topics of interest, 2) knowledge exploration, 3) analysis process, 4) application of knowledge or real-life practices, 5) conclusion and effective knowledge presentation, and 6) reflection process within learners or self-assessment. Through the integration of various important theoretical concepts, an effective learning management model has been created to promote analytical thinking skills among youths in the digital age.